(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article analyzes the methods of using integral indicators in assessing the ecological and biological state of soils of various degrees of salinity. In this study, soil biological activity was evaluated based on humus content, microbial abundance, enzymatic activity, carbon content, and salinity level (EC). The results indicate that as soil salinity increases, its biological activity declines. This phenomenon is attributed to intensified degradation processes, slowed organic matter turnover, and reduced soil fertility. Furthermore, the study confirms that biological methods are effective for evaluating the ecological condition of degraded soils using integral indicators. This approach provides a means to monitor and restore the biological stability of soils.